The Economic and Legal Sides of Additionality in Payments for Environmental Services - Karsenty, A.; Aubert, S.; Brimont, L.; Dutilly, C.; Desbureaux, S.; Ezzine-de-Blas, D.; Le Velly, G. (Wiley, 2017)
This paper aims to clarify two distinct but complementary questions on economic and legal additionality in the payments for environmental services (PES) debate based on examples from the literature and direct observations made in Madagascar and Mexico. For the economic dimension of additionality, we explain two ‘regimes of justification’, efficiency on the one hand and social equity on the other, and discuss how analysts position themselves with regard to both regimes. For the legal dimension, we review and analyse specific cases in which PES are implemented in addition to existing environmental regulations. We propose a renewed framework of analysis to distinguish ‘compensation’ and ‘reward’ in PES by crossing the opportunity cost dimension and the legal constraint vis‐à‐vis the environment. We show how difficult it is to fully maintain the objective of efficiency when PES are implemented simultaneously across different combinations of opportunity costs and regulation constraints. We propose policy options to address the contradiction between incentive and coercive instruments. These options are land sparing, social targeting and chronological combinations. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment